Smart Attendance System for University Students Based on QR Code - ABU SNEINEH Anees; SALAH Wael A. (Journal of Electrical and Electronics Engineering)
The aim of this paper is to solve the issue related to manual traditional attendance tracking for university students. This can be realized throughout setting up a new attendance system using quick response (QR) code. The developed system saving time while collecting students attendance at universities. The system is easy to use through a programmed user interface to create interaction between the user, the computer and the database. The proposed system structure includes electronic elements, Peripheral Interface Controllers (PIC) and a camera as a QR reader. The PIC microcontroller and the QR reader are connected to the computer through Universal Serial Bus (USB). When a student presents the ID card in front of a QR reader, the student's data is scanned using the algorithm described in this paper. The scanned data is then sent to PIC microcontroller for comparison with database, if this student is registered in that section, attendance records for that student are stored in database. Testing results of the developed system showed that the system satisfactory operated, saves time and reduces errors level.